Acehnese Archaic Words in Hikayat: An Early Influential Literary Work - Zulfadli Abdul Aziz; Syamsul Bahri Yusuf; Faisal Mustafa; Siti Munawarah (Bina Nusantara University, 2020)
The research aimed at finding out the Acehnese archaic words and their non-archaic alternatives that younger speakers often utter today. Several Acehnese original lexical items were no longer understood by the younger generation, and thus it was expected that some words to disappear without proper documentation. Hikayat Prang Sabi (Sabil War Sage), an early literary work in Acehnese, was the source of archaic words for the research. Therefore, the research design applied a descriptive qualitative method. The data consisted of 54 suspected archaic words from Hikayat Prang Sabi that were distributed to 20 speakers of Acehnese who lived in the Pidie regency. They were divided into two age groups consisting of 20 to 25 years old and 26 to 30 years old. They were asked to verify the suspected archaic words. The research results show that there are five archaic words and 49 semi-archaic words have found in the Hikayat.